Observation of excited Ω0c baryons in Ω−b→Ξ+cK−π− decays - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2021, 2021)
Title screen